An auto sorting waste detection service system for green society - Ahda, Sabrina Washiatul; Belal, H. M. (2017)
From the macro perspective, we can see waste as phenomenal volume of mixed complex materials and become a useless output if we do not put it into the step of circular solution which is recycle, reuse and reduce (3R). However, before that it must be in under process of sorting the waste by separating them into organic, inorganic and recyclable, unrecyclable to make the process of 3R more effective.Usually most of people are less awareness or not more knowledgeable to sorting their waste at source and there are no space as well as time to do sorting.This study proposes an effective and prominent system to sorting and detecting trash which is a modern sorting trash detection machine.The study planned to acquire by qualitative method, and obtain information through interview with the expertise of solid waste management.This research helps to improve the realization of the mandatory source separation from Malaysia government and the implementation of Act 672 about waste separation at source and recycling in Malaysia.